THE EFFECT OF FRAUD HEXAGON ON FINANCIAL STATEMENT FRAUD IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) IN 2017-2021 - Mayla Alyani; Indra Satria; Sri Irviati Wahyoeni (FEB-UP Press, 2023)
This research aims to determine the effect of hexagon fraud proxied by external pressure, change in directors, political connections, nature of industry, change in auditors and frequent number of CEO picture on financial statement fraud. This research uses quantitative research methods. The sample in this study was selected using a purposive sampling technique which obtained 13 property and real estate sector companies listed on the Indonesia Stock Exchange in 2017-2021 with a total sample of 65. Data collection techniques in this study using documentation techniques and library research. The data collected is the company's financial reports and annual reports. Data analysis technique used logistic regression analysis with Eviews 12 software. The results showed that external pressure, nature of industry and change in auditors had an effect on financial statement fraud, while changes in directors, political connections, and frequent number of CEO picture had no effect on financial statement fraud.